In Vitro Antagonistic and Fungicidal Activity against Agroathelia rolfsii (syn. Sclerotium rolfsii), the Causal Pathogen of Stem Base Rot Disease in Brassica Plants - Munthe, Muhammad Alwi; Novita, Aisar; Baharom, Nur Adliza (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2026)
Plants of the Brassica genus, such as cabbage, cauliflower, and broccoli, are high-value horticultural commodities that are susceptible to collar rot caused by the fungus Agroathelia rolfsii (syn. Sclerotium rolfsii). This soil-borne pathogen is difficult to control due to its ability to form sclerotia that can survive for long periods in the soil, thus requiring more effective and environmentally friendly alternative control strategies. This study aimed to evaluate the antagonistic activity of several Trichoderma spp. isolates and the effectiveness of two commercial fungicides, chlorothalonil and pencycuron, against A. rolfsii in vitro. The antagonism test was conducted using the double culture method, while the fungicide test used the toxic agar technique. The results of the study showed that Trichoderma sp. isolate T01 showed the highest antagonistic activity with a PGI value of 62.05%. However, this value was not significantly different from Trichoderma sp. isolate T2 (59.87%) and Trichoderma asperellum MHR1 strain (59.09%) based on the DMRT test. Meanwhile, among the fungicides tested, chlorothalonil at a concentration of 100 mg/L provided the highest inhibition of 21.98% and 10 mg/L (14.60%). These findings indicate that Trichoderma sp. isolate T01 has the potential to be used as an effective biological agent, while chlorothalonil can play a role as a supporting fungicide in the application of Integrated Pest Management (IPM) strategies. Further research is recommended to evaluate the effectiveness of both agents under greenhouse and field conditions to ensure consistency in their performance.